Sub-national Revenue Mobilization in Latin American and Caribbean Countries: The Case of Colombia - Fabio Sanchez Torres; Irina Espaa Eljaiek; Jannet Zenteno Gonzalez (Inter-American Development Bank (IDB), 2012)
This paper surveys the evolution and implications of fiscal decentralization in Colombia in recent decades. After describing the fiscal decentralization process and its impact on sub-national finances, the paper presents the evolution of departmental public finances, departmental vertical imbalances and the proposal to levy a VAT surcharge and a retail sales tax for the departments. The paper subsequently describes the evolution of municipal finances and municipal vertical imbalances, then includes calculations of the effective rates of the property and land tax and the industry and commerce tax, estimating the municipal tax burden, the efficiency rate of tax collection, and the determinants of both. The paper concludes with policy recommendations.
Keywords: H3; H7; H71; 330